(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Lipid-based drug delivery systems are extensively reported in literature for enhancing the drug solubility, permeability and bioavailability. These systems include simple oil solutions, coarse, multiple and dry emulsions, complex self-emulsifying, microemulsifying or nanoemulsifying drug delivery systems. Self-emulsifying systems are further classified as self-microemulsifying drug delivery systems (SMEDDS) and self-nanoemulsifying drug delivery systems (SNEDDS) are most prevailing and commercially viable oil based approach for drugs that exhibit low dissolution rate and inadequate absorption. Ever since the progress of SNEDDS, they drew the interest of researchers in order to deal with the challenges of poorly water-soluble drugs. SNEDDS is a proven method for enhancing solubility and bioavailability of lipophilic compounds. Considering the ease of large-scale production and the robustness of SNEDDS, several formulations techniques are commercially available. The stability of SNEDDS can be further enhanced by solidifying liquid SNEDDS. Controlled release and supersaturated SNEDDS received patient compliance with larger drug loading. Presence of biodegradable ingredients and ‘drug-targeting opportunities’ facilitate SNEDDS a clear merit and distinction amongst available solubility enhancement techniques. In this article attempt was made to present an overview of SNEDDS, their mechanism, formulation excipients and potentials of SNEDDS, recent advancements, advantages and disadvantages of SNEDDS formulations. The article also focuses on reviewing the application of SNEDDS in enhancing bioavailability of antihypertensive drugs.